Pequi peel flour in diets for Japanese quail - Oliveira, Maria Cristina de; Silva, Diones Montes da; Marchesin, Wilson Aparecido; Attia, Youssef Abd El-Wahab; Lima, Sarah Carvalho Oliveira; Oliveira, Higor Castro (Acta Scientiarum. Animal Sciences, 2016)
This study was carried out to evaluate the effects of pequi peel flour (PPF) in the diet of laying Japanese quails on their productive performance and on the quality and cost of the eggs produced. A total of 160 quail (Coturnix coturnix japonica) were distributed in a completely randomized design with four treatments and five replicates with eight birds each. Treatments consisted of different levels of PPF (0, 1, 2 and 3%) in a commercial diet based on sorghum. Evaluated parameters were productive performance (daily feed intake, laying rate, egg weight, egg mass and feed conversion rate), egg quality (yolk, albumen and eggshell weight and measures, yolk colour, ash and calcium content of eggshell, specific weight, Haugh unit, and nutrient content of the egg) and average cost of the production. PPF did not affect (p > 0.05) productive performance and nutritional composition, quality or average cost of the eggs; however, yolk colour was linearly increased (p < 0.05) with the PPF levels in the diets. It was concluded that PPF might be included in the commercial diets of Japanese quails up to 3% due to the improvement in yolk colour.